Numerical solution of stochastic and fractional competition model in Caputo derivative using Newton method - Meihua Huang; Pongsakorn Sunthrayuth; Amjad Ali Pasha; Muhammad Altaf Khan (AIMS Mathematics, 2022)
Many useful numerical algorithms of the numerical solution are proposed due to the increasing interest of the researchers in fractional calculus. A new discretization of the competition model for the real statistical data of banking finance for the years 2004–2014 is presented. We use a novel numerical method that is more reliable and accurate which is introduced recently for the solution of ordinary differential equations numerically. We apply this approach to solve our model for the case of Caputo derivative. We apply the Caputo derivative on the competition system and obtain its numerical results. For the numerical solution of the competition model, we use the Newton polynomial approach and present in detail a novel numerical procedure. We utilize the numerical procedure and present various numerical results in the form of graphics. A comparison of the present method versus the predictor corrector method is presented, which shows the same solution behavior to the Newton Polynomial approach. We also suggest that the real data versus model provide good fitting for both the data for the fractional-order parameter value ρ=0.7. Some more values of ρ are used to obtain graphical results. We also check the model in the stochastic version and show the model behaves well when fitting to the data.